2017
DOI: 10.1007/s00403-017-1731-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of palmitoyl-KVK-L-ascorbic acid on skin wrinkles and pigmentation

Abstract: Wrinkle formation and abnormal pigmentation are major clinical alterations associated with skin aging. As the aim of our study was to investigate the effects of palmitoyl-KVK-L-ascorbic acid on skin aging, the anti-wrinkle and depigmentation effects of palmitoyl-KVK-L-ascorbic acid were evaluated by measuring collagen expression in dermal fibroblast cells and inhibition of melanogenesis in B16F1 cells, respectively. The anti-aging effect of palmitoyl-KVK-L-ascorbic acid cream was also evaluated against a place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The chemical modification of the hydroxyl group at the C-2 position of ascorbic acid produced stable derivatives such as 2-O-α-D glucopyranosyl-L-ascorbic acid (ascorbic acid 2-glucoside) [ 140 , 141 ]. Conjugated form of palmitoyl-KVK and ascorbic acid (palmitoyl-KVK-L-ascorbic acid) to enhance stability and skin penetration of ascorbic acid not only increased type I collagen synthesis in dermal fibroblasts but also improved facial wrinkles and pigmentation in vivo [ 142 , 143 ]. Ascorbic acid encapsulated into negatively charged liposomes exhibited increased stability, skin permeation [ 139 ].…”
Section: Application In Skin Rejuvenationmentioning
confidence: 99%
“…The chemical modification of the hydroxyl group at the C-2 position of ascorbic acid produced stable derivatives such as 2-O-α-D glucopyranosyl-L-ascorbic acid (ascorbic acid 2-glucoside) [ 140 , 141 ]. Conjugated form of palmitoyl-KVK and ascorbic acid (palmitoyl-KVK-L-ascorbic acid) to enhance stability and skin penetration of ascorbic acid not only increased type I collagen synthesis in dermal fibroblasts but also improved facial wrinkles and pigmentation in vivo [ 142 , 143 ]. Ascorbic acid encapsulated into negatively charged liposomes exhibited increased stability, skin permeation [ 139 ].…”
Section: Application In Skin Rejuvenationmentioning
confidence: 99%
“…The use of anti‐aging cosmetics with vitamin C has increased in the last decade mainly due to their beneficial effects in preventing and minimizing the signs of skin aging 39 . The topical application of cosmetic goods containing 5%‐20% vitamin C promotes facial rejuvenation reducing wrinkles and erythema and increasing skin elasticity in volunteers 40‐42 . In human skin in vivo and pig skin, the topical application of aqueous solution containing 15% vitamin C and stabilized with 1% vitamin E and 0.5% ferulic acid at low pH (as observed in formulation 1 and 2) reduces UVA radiation–induced erythema 20,22 .…”
Section: Discussionmentioning
confidence: 99%
“…39 The topical application of cosmetic goods containing 5%-20% vitamin C promotes facial rejuvenation reducing wrinkles and erythema and increasing skin elasticity in volunteers. [40][41][42] In human skin in vivo and pig skin, the topical application of aqueous solution containing 15% vitamin C and stabilized with 1% vitamin E and 0.5% ferulic acid at low pH (as observed in formulation 1 and 2) reduces UVA radiation-induced erythema. 20,22 In addition, the administration of vitamin C in the medium protects reconstituted human epidermis or keratinocyte 3D cultures against DNA damage, inflammation, and apoptosis induced by UVA and UVB radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C (VC), also known as ascorbic acid, is a water-soluble vitamin essential for a number of processes in human skin, such as dermal collagen synthesis, antiaging, and antioxidation [24]. Emerging evidence has indicated that VC and its derivatives exert therapeutic effects on recalcitrant melasma and facial hyperpigmentation [5, 6], but little is known about their antipigmentary mechanism(s).…”
Section: Introductionmentioning
confidence: 99%